2020
DOI: 10.1002/adem.202001005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post‐heat Treatment on the Tensile and Cryogenic Impact Toughness Properties of Inconel 718 Manufactured by Selective Laser Melting

Abstract: This study investigates the effect of post‐heat treatments (solution treatment + aging [SA] and hot isostatic pressing + aging [HIPed]) on the tensile property as well as the room temperature and cryogenic impact toughness of Inconel 718 alloy manufactured by selective laser melting (SLM). The porosities of the three specimens measure SLM SA: 1.10% and SLM HIPed: 0.06%, and wrought SA: 0.01%. Initial microstructural observation shows γ″ + γ′ phase in all three alloys (SLM SA, SLM HIPed, and wrought SA). SLM SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…SLM samples revealed half of the ductility value compared with ACR samples, as was also shown in [35]. A similar problem was observed in the determination of notch toughness at room temperature (see Figure 16).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…SLM samples revealed half of the ductility value compared with ACR samples, as was also shown in [35]. A similar problem was observed in the determination of notch toughness at room temperature (see Figure 16).…”
supporting
confidence: 77%
“…However, the production of parts from Inconel 718 by additive manufacturing is very promising from the point of view of the very low machinability of the material. SLM samples revealed half of the ductility value compared with ACR samples, as was also shown in [35]. A similar problem was observed in the determination of notch toughness at room temperature (see Figure 16).…”
supporting
confidence: 77%
“…Vertical samples (ZX) had the poorest fracture toughness, horizontal XZ samples the best Results were attributed to tensile stress-strain response XZ samples were also noted to contain lower porosity [130] AlSi10Mg K IC calculated from fatigue fracture surfaces for vertical, diagonal and horizontal samples were 12.8 MPa m 0.5 vs 13.1 MPa m 0.5 and 14.0 MPa m 0.5 , respectively LoF pores along melt-pool boundaries aided crack propagation in vertical samples [151] AlSi10Mg Horizontal Charpy samples contain more gas pores but performed better than vertical samples due to microstructural reasons-cracks go across rather than along melt-pool boundaries Pores enlarged during T6 caused toughness to decrease and horizontal samples now performed worse than vertical samples Attributed to pores causing cracks to deviate from their usual path and the reduced load-bearing section area HIP ? T6 mitigated the pore growth issue, but Si coarsening limited toughness improvements (i) coalescence of porosity during impact [149], (ii) altering of the crack propagation path from one based on microstructure toward one based on porosity distribution [150,151], (iii) increased stress-concentration effects [75], and (iv) a substantial reduction in the actual cross-sectional area occupied by material that is available to absorb impact energy [148]. Thus, when Wang et al surveyed existing literature on the impact toughness of LPBF 316L and found a wide scatter in the impact toughness, as shown in Fig.…”
Section: Ref Alloymentioning
confidence: 99%